Equine chorionic gonadotrophin (eCG) after weaning in reproductive performance of sows from distinct parturition order - Brogni, Cláudio Francisco; Ohlweiler, Lain Uriel; Mezzalira, Joana Claudia; Mezzalira, Alceu (Revista Acadêmica Ciência Animal, 2020)
The weaning to estrus interval (WEI) and litter size are points that influences sow reproductive parameters and consequently the swine production. This study evaluated the effect of equine chorionic gonadotrophin (eCG), applied 5 hours after weaning, in sows of 1st to 5th parturition order (PO1-5) and sows with parturition order equal to or greater than 6 (PO6+) on reproductive parameters. PO1-5 sows (n = 240) were allocated into three groups: control group (n = 80), received 4 ml of saline solution; eCG800 group (n = 80), received 800 UI of eCG; and eCG1000 group (n = 80), received 1000 UI of eCG. PO6+ sows (n = 160) were allocated in control group (n = 80), receiving 5 ml of saline solution, and eCG1000 group (n = 80), that received 1000 IU of eCG. The estrous duration and litter parameters (mean weight, number of piglets per litter, number of live piglets, stillborn and mummified), insemination number and parturition order were evaluated. Chi-square test and analysis of variance with Tukey test were used in MIXED procedure of statistical package SAS (p < 0.05). An increased estrus duration and a mean increase of 1.5 piglets per litter was observed in eCG1000 group of PO1-5 sows, without affecting their mean weight. For PO6+ sows, the eCG1000 group was increased by one piglet per litter without interfering in the mean weight at birth. The economic analysis revealed a revenue of 400% of eCG investment in the PO1-5 sows, and 268% in the PO6+ group. It was concluded that the use of 1000 UI of eCG improves the reproductive parameters of sows of both (PO1-5 and PO6+) parturition orders.